NON-PRESCRIPTION OVERUSE OF NON-STEROIDAL DENTAL MEDICATIONS (مجلة البحوث الأكاديمية, 2023)
Introduction: Dental clinics are seeing a lot of individuals who need treatments for severe diseases. Almost all of these individuals self-medicate with non-prescription analgesics (NPA), and others mistakenly overdose on these medications to get treatment Further, individuals may not know the correct dose to use on their own and they may overdose inadvertently on other analgesics which can lead to nausea, vomiting, and respiratory problems. Objective: The study's objective is to provide information on how dental analgesics are administered to patients and any detrimental effects that may result from long-term overuse. Materials: The questionnaire was given to dental patients who use non-steroidal analgesics without a prescription. The study involved 102 patients, comprising 41 males and 61 females. The data came from individual patient interviews, and the majority of the questions received thorough, reliable answers. Results: Panadol is the most widely used analgesic type in the research sample, and its usage was 4% of the total (37.3%). Ibuprofen is one of the most problematic analgesics, with 30 cases in which users admitted that the drug was a problem. The majority of dental patients (76.5%) use the analgesic that was prescribed by the dentist in an organized manner, compared to 37.2% who do not. 6.9% use the balm for three to four days, and 14.7% use it for five days, while (14.7%) use it more. Conclusion: The most popular over-the-counter analgesics include Panadol, Ketofan, Ibuprofen, and Saridon.
Keywords: Dental analgesics; Uncertain non-sample prior information; steroidal Anti